Progesterone Increases Apoptosis and Inversely Decreases Autophagy in Human Hepatoma HA22T/VGH Cells Treated with Epirubicin - Wen-Tsan Chang; Hsiao-Ling Cheng; Bau-Shan Hsieh; Chien-Chih Chiu; King-Teh Lee; Kee-Lung Chang (The Scientific World Journal)
Hepatocellular carcinoma (HCC) is the leading cause of cancer-related deaths worldwide. Epirubicin can induce intracellular reactive oxygen species and is widely used to treat unresectable HCC. Progesterone has been found to inhibit the proliferation of hepatoma cells. This study was designed to test the combined effects of epirubicin and progesterone on human hepatoma cell line, HA22T/VGH. These cells were treated with different concentrations of epirubicin with or without the coaddition of 30 μM progesterone and then analyzed for apoptosis, autophagy, and expressions of apoptotic-related proteins and multidrug-resistant gene. Epirubicin treatment dose-dependently inhibited the growth of HA22T/VGH cells. Addition of 30 μM progesterone, which was inactive alone, augmented the effect of epirubicin on the inhibition of growth of HA22T/VGH cells. Cotreatment with progesterone enhanced epirubicin-induced apoptosis, as evidenced by greater increase in caspase-3 activity and in the ratio of the apoptosis-regulating protein, Bax/Bcl-XL. The combination also caused a decrease in autophagy and in the expression of multidrug resistance-related protein 1 mRNA compared to epirubicin alone. This study shows the epirubicin/progesterone combination was more effective in increasing apoptosis and inversely decreasing autophagy on HA22T/VGH cells treated with epirubicin alone, suggesting that this combination can potentially be used to treat HCC.